Wellhead Protection and the Future Water Demands from Publc Wells in the City of Madison - Abdullah, Fnu; Lu, Boyuan (My University, 2018)
Ultimately, chemicals and other contaminants wasted on the ground will make their way to reach the groundwater or aquifer and that way these pollutants will make the ground water unsafe for drinking. Where does uncertainty about groundwater came from? Groundwater pollution most often results from inappropriate disposal of wastes and the landuse management. It can also accrue naturally due to the presence of chemical elements in the aquifer layers. But the majority of groundwater contamination comes from human activities. There might be several reasons such as population growth, urbanization, rainfall, landuse management ...etc., that has an impact on the groundwater quantity and quality across the nation, but having good quality, safe drinking water at a reasonable cost is something that most people want, especially if their water comes from a public water supply system. In this paper, we are mainly focusing on a few components that might affect the quantity and quality of groundwater in the city of Madison, Wisconsin. Madison is relatively a rapidly growing city and as of July 1, 2016, Madison's estimated population of 252,551 made it the second largest city in Wisconsin. According to the Demographic Service Center of Wisconsin “City of Madison is estimated to have the fasted proportional growth of 7.23% from 2010 - 2017”. Potential consequences of rapid population growth include groundwater depletion and contamination. To make sure the groundwater quantity and quality is safe from human activities. Our goal in this project is to estimate the Wellhead Protection Area, Well Recharge Area and the future water demands from Madison wells in the next 50 years.
Includes Figures, Charts, Equations, Diagrams, Maps and Bibliography.
Keywords: Madison, Wisconsin; Water demands; Public water wells; Wellhead Protection Area; Groundwater